Individual variation in urinary sodium excretion among adolescent girls on a fixed intake. Issue 7 (July 2016) - Weaver, Connie M.; Martin, Berdine R.; McCabe, George P.; McCabe, Linda D.; Woodward, Mark; Anderson, Cheryl A.M.; Appel, Lawrence J.
Abstract : Background: According to traditional understanding of sodium homeostasis, nearly all of daily sodium intake is excreted in urine, with intraindividual variability attributed to variability in dietary sodium intake and urine collection errors. Objective: To analyze the variability of urinary sodium in excretion from a balance study with fixed sodium intakes. Methods: Daily 24-h urine collections were assessed for sodium, potassium, and creatinine in 22 black and 13 white adolescent girls (11–15 year, BMI 15–29 kg/m 2 ) in a randomized, crossover design with controlled diets containing either low (57 mmol/day) or high (167 mmol/day) sodium, each fed for 3 weeks. Results: Coefficient of variation analysis indicated higher variation in urinary sodium excretion about the mean on low (vs high) sodium (40 vs 32%, P  = 0.02) and in black (vs white) girls (42 vs 30%, P  < 0.001). A mixed model showed no sodium intake × race interaction. Urinary sodium excretion was not correlated with urinary potassium or creatinine excretion. Excretion of 65 mmol/day (adequate intake) or less was documented on 16% on the days during the high-sodium diet. Reliability of the mean of several urine sodium samples varied from 23% for one sample to 75% for 10 samples for the high-sodium diet. Conclusion: The high intraindividual variability in urinary sodium excretion on a fixed diet highlights the potential for substantial error in (a) using a single 24-h urine collection to estimate an individual's usual sodium intake and (b) relating sodium excretion from a single 24-h collection with outcomes. Further research is warranted to understand the causes of such variation.